Variability of selected quantitative traits in new spring barley genotypes - Wiśniewska, Magdalena; Fraś, Anna; Dmoch, Agnieszka (Plant Breeding and Seed Science, 2021)
The research included 19 breeding lines and 4 cultivars of spring barley from the preliminary field experiments harvested in 2020 in Radzików. All barley samples were characterized for the content of protein, non-starch polysaccharides (NSP) with soluble (S-NSP) and insoluble (I-NSP) fractions and β-glucan. Additionally, viscosity of water extracts (WEV) was measured to determine the functional properties of the grain. It was the most diverse parameter (CV = 27%) and was significantly correlated with β-glucan content (r = 0.50; for p <0.05). This dependence is shown by the results obtained for the grain of the Avatar cultivar and the RAH 744/19 breeding line, in which the content of β-glucan (5.3% and 4.8%, respectively), as well as the WEV (3.3 mPa.s and 3.0 mPa.s, respectively) were the highest. The lowest content of β – glucan (3.5%) and one of the lowest WEV values (1.4 mPa.s) were observed for KWS Jessie cultivar. Principal component analysis (PCA) showed a substantial impact of the two components PC1 and PC2 on the variability of the analyzed material showing significant variability of the 5 barley genotypes and confirmed the previous results of biochemical analyzes. Our results made it possible to indicate several genotypes that may constitute a source of variability in breeding works aimed at improving the quality of barley. Presented study also show that the grain of some new barley genotypes, with a favorable chemical composition from a fodder and brewing perspective, is a good material for future use in industry.